Uji Total Fenolik dan Aktivitas Antioksidan Ekstrak Batang Bajakah (Spatholobus littoralis Hassk.) - Sari Wulan; Occa Roanisca; Nurhadini Nurhadini (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
Diseases in the human body can be caused by free radicals. Environmental conditions and unhealthy lifestyles cause the human body's defense system against free radicals to become weaker, so it is necessary to have external antioxidants to help ward off free radicals. Therefore, it is necessary to have natural antioxidants from plants in overcoming free radicals. This study aims to determine the levels of phenolic contained in the ethanol extract of bajakah stems and their potential bioactivity as antioxidant. Determination of phenolic content was carried out using the Folin-Ciocalteau method and antioxidant testing was carried out using the DPPH method. The total phenolic test results obtained were 21.535 mg EAG/g. The antioxidant test of the ethanol extract of the bajakah stem showed weak activity with an average IC50 value of 281,717 g/mL.